2003
DOI: 10.1038/nature02002
|View full text |Cite
|
Sign up to set email alerts
|

Episodic sediment accumulation on Amazonian flood plains influenced by El Niño/Southern Oscillation

Abstract: Continental-scale rivers with a sandy bed sequester a significant proportion of their sediment load in flood plains. The spatial extent and depths of such deposits have been described, and flood-plain accumulation has been determined at decadal timescales, but it has not been possible to identify discrete events or to resolve deposition on near-annual timescales. Here we analyse (210)Pb activity profiles from sediment cores taken in the pristine Beni and Mamore river basins, which together comprise 720,000 km2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
272
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(285 citation statements)
references
References 23 publications
11
272
1
1
Order By: Relevance
“…River floodplain deposits, for example, have a large advection length scale ( Fig. 4; Supplementary Table 1) and have been shown to record metrics for flood discharge on annual to decadal timescales in the absence of morphodynamic filtering 45 . The connection between signal preservation and planar beds also lends support for the often-used assumption of a direct, linear connection between orbital forcing and bed-thickness patterns in horizontally laminated strata on Mars 48 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…River floodplain deposits, for example, have a large advection length scale ( Fig. 4; Supplementary Table 1) and have been shown to record metrics for flood discharge on annual to decadal timescales in the absence of morphodynamic filtering 45 . The connection between signal preservation and planar beds also lends support for the often-used assumption of a direct, linear connection between orbital forcing and bed-thickness patterns in horizontally laminated strata on Mars 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows examples in the advection regime where morphodynamics did not develop and where the sedimentary strata faithfully recorded allogenic forcing. In the advection regime (unlike the saturation regime), it is large systems that transport fine sediment that likely record environmental signals over the largest range in scales, potentially including preservations of signals that manifest over kilometres in length 45 (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…In these large, accumulating floodplains of the Beni and Mamoré, present-day rates of sediment deposition are enormous (Guyot, 1993;Guyot et al, 1996;Aalto et al, 2003). From measuring suspended sediment concentrations in the Andean and floodplain Beni basin, Guyot (1993) and Guyot et al (1996) for example found that about half of the total sediment flux discharged from the Bolivian Andes is deposited in the adjacent Beni foreland basin.…”
Section: Study Areamentioning
confidence: 99%
“…The Beni River is an upper Amazon tributary; its floodplain is a thoroughly investigated system where modern migration rates, recent sediment discharge, and bank erosion rates are well known (Guyot et al, 1996;Aalto, 2002;Aalto et al, 2003;Gautier et al, 2007). 10 Be concentrations of Beni River floodplain sediment have also been investigated in detail (Wittmann, 2008).…”
Section: The Beni River Examplementioning
confidence: 99%